MAGNETIZATION OF STARS VS. THE EFFECTIVE TEMPERATURE - Bychkov, V. D.; Bychkova, L. V.; Madej, J. (Одеські астрономічні публікації, 2008)
Using all published magnetic measurements there were detected some dependences of frequency of occurrence of magnetic field value for all types of peculiarity (Bychkov et al., 2003a, 2008). On the basis of it we normalized these dependences for the most "non-magnetic" Am-stars and we draw the relative "magnetization" (MA) for peculiarity types for Ap-stars (Bychkov et al., 2003b). At the same time chemically peculiar stars neatly block to the two groups: "weak" - magnetic (Am and Hg-Mn stars) and "strong" - magnetic (SrCrEu, Sr, Si, He-w and He-r stars). "Strong" - magnetic group outnumbers "weak" magnetic group on magnetic activity on average 5-10 times more, as shown in Fig. 3. This is mathematical expression of well-known observing fact. One of the most important and simpliciter measurable physical characteristic of stars atmospheres is effective temperature. This paper is devoted to the dependence of "magnetization" on Teff